Hubungan Kadar HDL dengan Defisit Neurologis Selama Perawatan pada Pasien Stroke Iskemik - Mahardhika, Dyah Resti, Dr. Iwan Setiawan, Sp.S (2017)
Stroke is a serious neurological disease and the mortality rate is quite high. Effect of dyslipidemia to increased stroke risk factors associated with high levels of LDL and low HDL levels. A decrease in the HDL levels can affect patients with ischemic stroke neurological deficit due process of atherosclerosis. Previous research remains controversial and requires further research. This research aims to examine the correlation between HDL levels and neurological deficit during treatment to patients of ischemic stroke. This is an observational analytic study with cross sectional approach. The sample was taken with the principle of purposive sampling with ischemic stroke patients are undergoing treatment at PKU Aisyiyah Boyolali Hospital and PKU Muhammadiyah Hospital Delanggu in November-December 2016. Data were analyzed with Chi-Square test. A total of 13 patients with ischemic stroke with low HDL levels showed 6 patients (23.1%) with mild neurological deficit and 7 patients (26.9%) with a moderate deficit, while 13 ischemic stroke patients with normal HDL levels obtained 7 patients ( 26.9%) with mild deficit and 6 patients (23.1%) with a moderate deficit. Result of statistical analysis using Chi-Square test obtained by value p = 0.695. There is no significant correlation between the levels of HDL with neurological deficit during treatment in patients with ischemic stroke.